2006
DOI: 10.1128/jcm.44.3.1098-1100.2006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Testing Methods for Detection of Decreased Linezolid Susceptibility Due to G2576T Mutation of the 23S rRNA Gene in Enterococcus faecium and Enterococcus faecalis

Abstract: E-test, Vitek 2, MicroScan, agar dilution, and disk diffusion were compared for detection of decreased linezolid susceptibility due to 23S rRNA gene G2576T mutation among 32 clinical Enterococcus strains initially reported as intermediate or resistant by E-test alone or Vitek 2 confirmed by E-test. Agar and broth dilution methods were in concordance with PCR detection of the mutation, and disk diffusion was somewhat less sensitive but equally specific.Linezolid provides high rates of clinical cure and microbio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 13 publications
1
38
0
Order By: Relevance
“…This is consistent with the report of Qi et al, who showed a high correlation between the presence or absence of mutations in the 23S rRNA gene and the phenotype reported by the MicroScan system (18). VITEK 2 also had high category agreement, provided that the advanced expert system, which reported all linezolid-nonsusceptible staphylococci as susceptible, was not used.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This is consistent with the report of Qi et al, who showed a high correlation between the presence or absence of mutations in the 23S rRNA gene and the phenotype reported by the MicroScan system (18). VITEK 2 also had high category agreement, provided that the advanced expert system, which reported all linezolid-nonsusceptible staphylococci as susceptible, was not used.…”
Section: Discussionsupporting
confidence: 80%
“…In one study, Qi et al noted that the linezolid resistance results reported for enterococci by the MicroScan system (with a PC-21 panel) correlated well with the presence of G2576T mutations in domain V of the 23S rRNA gene of the organisms tested. In that same study, however, the Etest and VITEK 2 methods (with an AST GP-61 card) tended to produce false resistance results when compared by using the results of rRNA sequencing as the "gold standard" (18). Problems with false linezolid resistance results for enterococci were also reported by Scheetz et al (19).…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…However, Qi et al did evaluate the ability of Etest, agar dilution, broth microdilution, disk diffusion, and Vitek2 to detect decreased linezolid susceptibility in enterococci with G2576T mutations (15). The purpose of the study by Qi et al was to assess the impact of G2576T mutation on phenotypic susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…However, a few reports documented resistance detection independent from linezolid treatment (Rahim et al, 2003;Bonora et al, 2006). Resistance results from point mutations in 23S rRNA, preferably at position 2576 (G > T) Werner et al, 2004;Qi et al, 2006;Werner et al, 2007a) and the level of resistance is dependent on the number of mutated alleles per genome (Marshall et al, 2002;Lobritz et al, 2003;BourgeoisNicolaos et al, 2007;Boumghar-Bourtchai et al, 2009). Once established, resistance levels quickly arise due to recombinational exchange of mutated 23S rDNA alleles under selective pressure (Willems et al, 2003;Boumghar-Bourtchai et al, 2009).…”
Section: Linezolid Resistancementioning
confidence: 99%